Struktura pola opadów Polski na tle warunków cyrkulacyjnych - Komar, Zbigniew (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The way circulation factors influence the spatial structure of the precipitation area in Poland was studied on the basis of everyday pluviometric data from 31 metrological stations as well as a circulation catalogue published by M. Stępniewska-Podrażka. The analysis covered all 7-day-long or longer periods which displayed the same type of circulation in the years 1951–1990. The pluviometric data gathered made it possible to characterise the pluviometric regimes for each town in the specified periods taking account of 3 factors: total precipitation, frequency of precipitation and intensity of precipitation. The study focused on pluviometric similarities between neighbouring points (stations) under specified conditions of atmospheric circulation. When considering matters related to the objective of the study, account was taken of the elements of the graph theory which not only made it possible to graphically represent the directions of similarity research but also showed the degree of consistency between pluviometric similarity networks from a statistical point of view. The research uncovered some particular features of structural organisation of the precipitation area depending on the conditions of atmospheric circulation: – Variation in similarity within the precipitation areas is disturbed to a different degree The number of similar relations in constructed graph networks varied between 9 and 75. – Cases of perfect similarity can be observed only under anti-cyclonic circulation and were present in SEa, Sa and Oa circulation types. – The degree of similarity within the precipitation area varies depending on the character of circulation. The mean frequency with which precipitation similarities were identified along studied edges is at its lowest under cyclonic circulation and at its highest under anti-cyclonic conditions. – When analyzed by seasons, the frequency of pluviometric precipitation similarity along specified relation lines was lower in the warm half-year under cyclonic, intermediate and anti-cyclonic circulation conditions. The graph method of studying structural features of the precipitation area used in this paper has proved to be a useful and effective research tool especially when applied to analyses of spatial relations. Presented examples of graphs are a more or less clear indication that the spatial structure of the precipitation area in Poland studied from the perspective of pluviometric similarity relations is determined by circulation factors with the spatial scope of this influence depending on the season.
Keywords: Poland; atmospheric precipitation; atmospheric circulation